Halal Lifestyle Based on Value Creation: Evidence in Valqo Leather Factory Micro Businesses, East Java - Hakim, Abdul; Yudha, Ana Toni Roby Candra; Dikuraisyin, Basar; Masrufa, Nur (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Nowadays, the potential for halal products continues to grow. This is also followed by the expansion of the halal lifestyle which is not only loved by Muslims but also non-Muslims. The purpose of this study is to examine and determine product development efforts and strategies through the theory of value creation according to the halal lifestyle in business units in Sidoarjo. The research method uses descriptive qualitative. This method involves informants from several parties, including business owners, customers, and the community around the company. In order to obtain the most current data and studies, we supplemented the research by adding Sinta indexed literature published over the last five years. The results showed that the efforts to develop halal fashion accessories were carried out by Valqo Leather Factory as a business unit in Sidoarjo, through value creation strongly supports the development process in fulfilling consumers' halal lifestyle. The value creation that results may influence hiring more staff members, raising product demand, and increasing product selling power. Suggestions that relevane to the results of the research are the need for further product development in the form of sales branch units, selection of raw materials, the aim of which is to expand the market to all circles and even generations with modern, practical and efficient products, while increasing public education and literacy on the halal life style. Saat ini, potensi produk halal terus berkembang. Hal ini juga diikuti dengan meluasnya gaya hidup halal yang tidak hanya digandrungi oleh umat Islam tetapi juga non-Muslim. Tujuan dari penelitian ini adalah untuk mengkaji dan menentukan upaya dan strategi pengembangan produk melalui teori penciptaan nilai sesuai gaya hidup halal pada unit bisnis di Sidoarjo. Metode penelitian menggunakan deskriptif kualitatif. Cara ini melibatkan informan dari beberapa pihak, antara lain pemilik usaha, pelanggan, dan masyarakat sekitar perusahaan. Sebagai pelengkap penelitian, kami juga menambahkan literatur terindeks Sinta yang diterbitkan dalam lima tahun terakhir, untuk memperoleh data dan kajian terkini. Hasil penelitian menunjukkan bahwa upaya pengembangan aksesoris produk halal yang dilakukan oleh Pabrik Kulit Valqo sebagai unit bisnis di Sidoarjo, melalui penciptaan nilai sangat mendukung proses pengembangan dalam pemenuhan gaya hidup halal konsumen. Penciptaan nilai yang dimunculkan mampu memberikan dampak meningkatnya permintaan produk, menambah karyawan baru dan memperluas daya jual produk. Saran yang relevan dengan hasil penelitian adalah perlunya pengembangan produk lebih lanjut berupa unit cabang penjualan, pemilihan bahan baku yang bertujuan untuk memperluas pasar ke semua kalangan bahkan generasi dengan cara yang modern, praktis dan efisien produk, sekaligus meningkatkan edukasi dan literasi masyarakat terhadap gaya hidup halal.